Upaya Meningkatkan Minat Belajar Peserta Didik Pada Pembelajaran Tematik Melalui Model Pembelajaran Project Based Learning Kelas II SD Negeri 1 Mataram - Nurwasilah Nurwasilah; Intan Triwahyuni; Syaiful Musaddat (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
The purpose of this study is to increase students' interest in topic-based learning through Project Based Learning (PjBL) model for Grade II SD Negeri 1 Mataram for the school year 2022/2023 with a total of 24 students. This type of inquiry is a collaborative classroom inquiry. The instrument used in this study was an observation sheet for students' interest in learning through the project-based learning (PjBL) model. The results of the study showed that students' interest in learning in thematic learning increased, as evidenced by the average score obtained in Cycle I, namely 3.13 in the medium category and the average score obtained in Cycle II, namely 3.95 in the high category. From the results of this study, it can be concluded that Project Based Learning (PjBL) model can enhance students' interest in learning in Class II Thematic Learning in SD Negeri 1 Mataram.